Leitura em Língua Portuguesa como segunda língua por surdos: uma análise da interpretação de metáforas - Ana Rachel Carvalho Leão (2020)
This study addresses how Brazilian deaf people whose first language is Libras and second language is Portuguese comprehend metaphor in Portuguese according to Conceptual Metaphor Theory. The general objective of this research, which has a qualitative nature, is to investigate whether the deaf, when reading multimodal texts in Portuguese as a second language that present something close to their reality, such as situations typical of deaf culture, understand the metaphorical meaning of a given word or expression without processing its literal meaning first. We invited deaf undergraduate students of Letras-Libras to participate in the research. First, we carried out an interview with personal questions in order to understand each participants’ relationship with Libras and Portuguese (where did they learn them, how old they were when they learned them, what type of school did they attend). After the interview, the texts were presented to participants in a previously established sequence. The data were collected individually with each participant. They had time to read each text and to think of a way of adapting it to Libras. The way each participant interpreted the text was filmed and transcribed in Portuguese. The eight metaphors used in the study are part of the conceptual metaphor inventory presented by Lakoff and Johnson ([1981] 2003). All the texts that compose this study are authentic, such as cartoons, comic strips and advertisings, in which we selected metaphorical expressions. All metaphorical expressions were analyzed according to Conceptual Metaphor Theory (LAKOFF, JOHNSON [1981] 2003). From the selected texts, we elaborated three tests in order to assess whether multimodal texts or texts taken from a context more significative for students – the context of deaf culture – would be better interpreted than texts with no multimodal support or without a significative context. The tests were applied in a predetermined order due to the fact that some presented facilitatory effects. In the first test, participants read a text written in Portuguese, with no connection to the context of deaf culture, and without visual supports of any kind. In the second test, the texts were written in Portuguese and presented images that could contribute to their interpretation. The texts selected for the last test had utterances in Portuguese and images, and both of them were drawn from the context of deaf culture, which is shared by all participants. Data analyses were performed qualitatively. We analyzed the way each participant interpreted the metaphors presented to them, as well as which metaphors were interpreted correctly and how many participants were able to interpret them in such manner. With our results, we wish to contribute to a better comprehension of how the deaf interpret metaphors in a second language, and also to the selection and development of educational materials for teaching reading in Portuguese as a second language to the deaf (PL2S).